Standards for Approval of Teacher Preparation Programs in Virginia. Revised - Virginia State Dept. of Education, Richmond; Virginia State Dept. of Education, Richmond ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
State regulations governing the accreditation of colleges of education in the state of Virginia are set forth. (JD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accreditation (Institutions); Certification; Institutional Evaluation; State Standards; Teacher Education Programs; Virginia; Legal/Legislative/Regulatory Materials